2008
DOI: 10.1162/jocn.2008.20011
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual and Monolingual Brains Compared: A Functional Magnetic Resonance Imaging Investigation of Syntactic Processing and a Possible “Neural Signature” of Bilingualism

Abstract: Does the brain of a bilingual process language differently from that of a monolingual? We compared how bilinguals and monolinguals recruit classic language brain areas in response to a language task and asked whether there is a "neural signature" of bilingualism. Highly proficient and early-exposed adult Spanish-English bilinguals and English monolinguals participated. During functional magnetic resonance imaging (fMRI), participants completed a syntactic "sentence judgment task" [Caplan, D., Alpert, N., & Wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(121 citation statements)
references
References 75 publications
10
109
2
Order By: Relevance
“…Our results were consistent with this U-shaped effect. It should be noted that, although our results were limited to temporary activation changes of the existing languages to accommodate the newly acquired language, long-term interactions between these languages are likely to continue, as shown by the comparisons between bilinguals and monolinguals (Kovelman et al, 2008; Rodriguez-Fornells et al, 2002) and brain changes in bilinguals (Mechelli et al, 2004; Mohades et al, 2012). …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our results were consistent with this U-shaped effect. It should be noted that, although our results were limited to temporary activation changes of the existing languages to accommodate the newly acquired language, long-term interactions between these languages are likely to continue, as shown by the comparisons between bilinguals and monolinguals (Kovelman et al, 2008; Rodriguez-Fornells et al, 2002) and brain changes in bilinguals (Mechelli et al, 2004; Mohades et al, 2012). …”
Section: Discussionmentioning
confidence: 93%
“…Thus far, only a few studies have examined how bilinguals and monolinguals differ in the neural processes of their native language. For instance, it has been revealed that the left inferior frontal gyrus is more involved in native language processing for bilinguals than for monolinguals (Kovelman et al, 2008; Parker Jones et al, 2012; Rodriguez-Fornells et al, 2002) and for more proficient bilinguals than for less proficient bilinguals (Nosarti et al, 2010). These results suggest that long-term second language learning can affect the neural basis of native language processing.…”
Section: Introductionmentioning
confidence: 99%
“…All participants also reported continual use of the two languages. Participants also completed a previously published Language Competence/Expressive Proficiency (LCEP) test (for details on test administration and scoring see Kovelman et al, 2008a,b,c; Berens et al, 2013). LCEP builds upon measures of sign language competence, originally established for the study of Nicaragual Sign Language (Senghas and Kegl, 1994), and was expanded for use with other sign and spoken languages (Petitto et al, 2001a; Schembri and Johnston, 2004; Jasinska and Petitto, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that unimodal spoken language bilinguals also typically show greater signal intensity in left inferior frontal regions during lexico-semantic (Kovelman et al, 2008c), syntactic (Jasinska and Petitto, 2013), and language switching tasks (Abutalebi et al, 2008; Kovelman et al, 2008c), relative to monolinguals. Yet, it remains generally unknown if these differences predominantly stem from frequent competition between bilinguals' two languages (Abutalebi et al, 2008) or the overall increase in language capacity to accommodate for two linguistic systems (Kovelman et al, 2008a). Research into bimodal bilinguals who potentially experience reduced competition between their two languages in non-overlapping auditory and visual modalities may shed new light on the nature of the brain's accommodation for two languages.…”
Section: Introductionmentioning
confidence: 99%
“…[…] both monolinguals (in one language) and bilinguals (in each language) showed predicted increases in activation in classic language areas […], with any neural differences between the bilingual's two languages being principled and predictable based on the morphosyntactic differences between Spanish and English […] suggesting that there may be a functional separation of a bilingual's two languages in one brain based on the formal linguistic properties of each given languages (Kovelman, Baker and Petitto, 2008, emphasis mine).…”
Section: Translated Rhetoric: From Particular Differences To Far-flunmentioning
confidence: 99%